OPTIMIZING ROAD SAFETY THROUGH GEOSPATIAL ANALYSIS OF ACCIDENT HOTSPOT CHARACTERISTICS AND VULNERABILITY LEVELS IN KARANGASEM REGENCY: GIS-Based Mapping and Analysis for Road Accident Prevention in Karangasem Regency - I Dewa Made Ari Praja Nugraha; Putu Alit Suthanaya; Putu Cinthya Pratiwi Kardita; Made Agus Ariawan; I Made Juwan Kusuma; Ni Kadek Juliani (Fakultas Sains dan Teknologi Universitas Ngurah Rai, 2026)
According to data published by the World Health Organization (WHO, 2018), approximately 1.35 million people die annually due to road traffic accidents. This equates to one life lost every 25 seconds. In addition to the loss of life, road traffic accidents also cause profound psychological trauma for victims and families who lose loved ones. This research aims to identify road vulnerabilities and characterize traffic accident incidents in Karangasem Regency while addressing the research gap through a geospatial-based accident hotspot analysis using QGIS. This approach has not been comprehensively conducted in previous studies to support the development of more targeted and effective road safety policies in line with SDG 9. The primary data for this research involved geospatial analysis of high-risk locations, including the Tebola, Budakeling, and Tulamben highways, as well as other road sections. Furthermore, geoinformatics analysis using a quantum geographic information system (QGIS) was conducted to map the distribution of incidents and identify accident-prone areas as secondary data. The evaluation showed that the severity of road accidents is closely related to driver behavior and the physical condition of the road. From 2018 to 2022, 1,613 traffic accidents were recorded, with motorcycles accounting for the largest proportion, at 80.47%. Side-impact collisions were the most common type, with 384 reported. Mondays saw the highest number of accidents, with 222 incidents. In total, there were 1,648 injuries and 168 deaths. Evaluations show that the severity of traffic accidents is closely related to driver behavior and road conditions.